Review of Neoperla (Plecoptera: Perlidae) from Guangdong Province of China - Li, Weihai; Wang, Guoquan; Li, Wenliang; Murányi, Dávid (Zootaxa, 2012)
Four species of the genus Neoperla known from Guangdong Province, China are reviewed. Two species are described as new: Neoperla flagellata sp. nov., and N. similiserecta sp. nov., and N. mnong Stark is recorded from the Province for the first time. Illustrations and color photographs are provided for each species, and the new species are compared to similar taxa.